The Development of Observation Module of Astronomy Lecture Based on Sky Portal Application - Tandra, Tan, Fahrur Rozy; Nuryadin, Atin; Sulaeman, Nurul Fitriyah (Universitas Negeri Semarang, 2025)
Astronomy is one of Physics’ branches. But, there is a content shift happening in Astronomy where it should be part of Physics, but currently it tends to be part of Geography. Hence, it is needed a module which can support deeper understanding in Astronomy through sky observation. This research aims to develop an Astronomy observation module based on Sky Portal Application which is valid and has a good response. This research used the ADDIE model with the students of Physics Education Study Porgram of Education and Teacher Training Faculty of Mulawarman University batch 2022 being the subject. The data was gathered by using the questionnaire for the validation of material and media, and also questionnaire for the response of the students. The material obtains a percentage of 89,3%, while the media obtains a percentage of 87,7%, which both of them are categorized as valid. Meanwhile, the response of the students obtains a percentage of 88,8% which is categorized as practical. So, from the results of validation and response of the Observation Module of Astronomy Lecture based on Sky Portal Application, this module is valid and can be used in the lecture activity.